Water Ice Radiolytic O2, H2, and H2O2 Yields for Any Projectile Species, Energy, or Temperature: A Model for Icy Astrophysical Bodies. Issue 10 (14th October 2017) - Teolis, B. D.; Plainaki, C.; Cassidy, T. A.; Raut, U.
Abstract: O2, H2, and H2 O2 radiolysis from water ice is pervasive on icy astrophysical bodies, but the lack of a self‐consistent, quantitative model of the yields of these water products versus irradiation projectile species and energy has been an obstacle to estimating the radiolytic oxidant sources to the surfaces and exospheres of these objects. A major challenge is the wide variation of O2 radiolysis yields between laboratory experiments, ranging over 4 orders of magnitude from 5 × 10 −7 to 5 × 10 −3 molecules/eV for different particles and energies. We revisit decades of laboratory data to solve this long‐standing puzzle, finding an inverse projectile range dependence in the O2 yields, due to preferential O2 formation from an ~30 Å thick oxygenated surface layer. Highly penetrating projectile ions and electrons with ranges ≳30 Å are therefore less efficient at producing O2 than slow/heavy ions and low‐energy electrons (≲ 400 eV) which deposit most energy near the surface. Unlike O2, the H2 O2 yields from penetrating projectiles fall within a comparatively narrow range of (0.1–6) × 10 −3 molecules/eV and do not depend on range, suggesting that H2 O2 forms deep in the ice uniformly along the projectile track, e.g., by reactions of OH radicals. We develop an analytical model for O2, H2, and H2 O2 yields from pure water ice for electrons and singly charged ions of any mass and energy and apply the model to estimate possible O2 source rates on several icy satellites. The yields are upper limits for icy bodies on which surface impurities may be present. Plain Language Summary: Ice‐covered comets and moons in the outer solar system are irradiated by charged particles from space, which break apart the surface water molecules to form hydrogen peroxide, as well as molecular hydrogen and oxygen which are ejected into the atmospheres of these objects. Here we develop a comprehensive model of the production of peroxide, hydrogen, and oxygen, versus the mass and energy of the charged particles, and the temperature of the ice. The model predicts self consistently the production rates of all three molecules as measured in laboratory experiments and enables quantitative predictions of the supply of these molecules to the surfaces and atmospheres of icy objects in space. Key Points: We give predicted yields for O2, H2, and H2 O2 radiolysis from ice for electrons and ions at any energy, (ion) mass, and ice temperature Lab experiments reveal an inverse range dependence in radiolytic O2 yields from ice with highly penetrating projectiles The model's predictions of icy satellite O2, H2 sources, and H2 O2 column densities can be compared to data to elucidate surface composition